NLRP3 Inflammasome Promotes Myocardial Remodeling During Diet-Induced Obesity - Sokolova, Marina; Sjaastad, Ivar; Louwe, Mieke C.; Alfsnes, Katrine; Aronsen, Jan Magnus; Zhang, Lili; Haugstad, Solveig B.; Bendiksen, Bård Andre; Øgaard, Jonas; Bliksøen, Marte; Lien, Egil; Berge, Rolf K.; et al. (Frontiers in Immunology, 2019)
Background Obesity is an increasingly prevalent metabolic disorder in the modern world and is associated with structural and functional changes in the heart. The NLRP3 inflammasome is an innate immune sensor that can be activated in response to endogenous danger signals and triggers activation of interleukin (IL)-1β and IL-18. Increasing evidence points to the involvement of the NLRP3 inflammasome in obesity-induced inflammation and insulin resistance, and we hypothesized that it also could play a role in the development of obesity induced cardiac alterations. Methods and results WT, Nlrp3−/−, and Asc−/− male mice were exposed to high fat diet (HFD; 60 cal% fat) or control diet for 52 weeks. Cardiac structure and function were evaluated by echocardiography and magnetic resonance imaging, respectively. Whereas NLRP3 and ASC deficiency did not affect the cardiac hypertrophic response to obesity, it was preventive against left ventricle concentric remodeling and impairment of diastolic function. Furthermore, whereas NLRP3 and ASC deficiency attenuated systemic inflammation in HFD fed mice; long-term HFD did not induce significant cardiac fibrosis or inflammation, suggesting that the beneficial effects of NLRP3 inflammasome deficiency on myocardial remodeling at least partly reflect systemic mechanisms. NLRP3 and ASC deficient mice were also protected against obesity-induced systemic metabolic dysregulation as well as lipid accumulation and impaired insulin signalling in hepatic and cardiac tissues. Conclusions Our data indicate that the NLRP3 inflammasome modulates cardiac concentric remodeling in obesity through effects on systemic inflammation and metabolic disturbances, with effect on insulin signalling as a potential mediator within the myocardium.